Electret‐Inspired Charge‐Injected Hydrogel for Scar‐Free Healing of Bacterially Infected Burns Through Bioelectrical Stimulation and Immune Modulation - Mujie Liu; Yuheng Wang; Haodong Wang; Lihong Qi; Yuxuan Shang; Jiajie Song; Xiulong Feng; Yiwei Chen; Waqar Ali Memon; Yuping Shen; Xiaodong Wu; Jiangbei Cao; et al. (Advanced Science)
Abstract In this study, an electret‐inspired, charge‐injected hydrogel called QOSP hydrogel (QCS/OD/SDI/PANI/PS/Plasma) that promotes scar‐free healing of bacteria‐infected burns through bioelectrical stimulation and immune modulation, is presented. The hydrogel, composed of quaternized chitosan (QCS), oxidized dextran (OD), sulfadiazine (SDI), polystyrene (PS), and polyaniline nanowires (PANI), forms a conductive network capable of storing and releasing electric charges, emulating an electret‐like mechanism. This structure delivers bioelectrical signals continuously, enhancing wound healing by regulating immune responses and minimizing fibrosis. In a mouse model of second‐degree burns infected with Staphylococcus aureus (SA) and Pseudomonas aeruginosa (PA), the hydrogel accelerates wound healing by 32% and reduces bacterial load by 60%, significantly inhibited scar formation by 40% compared to controls. QOSP hydrogel modulates the Th1/Th2 immune balance toward a Th1‐dominant antifibrotic state through quaternized chitosan, thereby reducing collagen deposition by 35%. Electro‐dielectric characterization reveals a dielectric constant of 6.2, a 34% improvement in conductivity (3.33 × 10−5 S/m) and a 30 °C increase in thermal stability. Proteomic analysis highlights a 50% down‐regulation of pro‐inflammatory and pro‐fibrotic pathways, suggesting a controlled immune response conducive to scar‐free healing. This study underscores the potential of bioelectrically active hydrogels as a novel approach for treating infected wounds prone to scarring.